Graphic design education and the importance of selected Malaysian cultural art forms / Yip Jinchi - Yip , Jinchi (2019)
Bauhaus was a German school of design that set the benchmark for worldwide graphic design education from the early 20th century till today. While the principles of graphic design are a sure guideline for students to abide by when producing graphic works, the researcher has found through experience that much of their graphic work lack local art forms in their content. Using a case study action research approach, the research first explored an initial group of 20 graphic design students’ initial understanding of their knowledge of Malaysian Cultural Art Forms (MCAF). Then intervention activities that incorporated MCAF in the Malaysian graphic design class were implemented after which the students understanding of their knowledge in MCAF were determined. Finally, expressions of cultural identity were elicited. The students were from a private university in Selangor. After the findings from the initial group emerged, it mooted an idea that the expressions of cultural identity by students who did not experience the intervention activities should be compared with the group that had the experience. Thus, the whole study was a four-cycle case study action research. In Cycle 1, the researcher conducted a focus group interview and administered questionnaires to gauge students’ initial understanding of MCAF. In Cycle 2 intervention activities were incorporated into the classroom learning. The interventions included, a visit to a contemporary Malaysian art exhibition; participation in a batik workshop; a visit and hands-on experience making some craft work at a Mah Meri cultural village, and attending a talk about wayang kulit, as well as viewing some wayang kulit exhibits. Upon the completion of each activity, the students had to answer a questionnaire with regards to their learning and understanding of each of the MCAF. Upon the completion of the interventions an open-themed project was given to the students where they were to identify a local social/health/environmental issue and produce a visual solution, based on their exposure to the four MCAF. From the students’ work, rationale and reflection, and a focus group interview at Cycle 3, the researcher studied their expressions of cultural identity. In Cycle 4, the researcher gave an open-themed project (but in greater contextual detail) to a second group of students without the intervention activities for comparison. Findings show that the first group of students did not have much knowledge nor understanding of MCAF before participating in the intervention activities. However, the students understanding deepened together with their expressions of cultural identity after participating in the intervention activities. As for the second group without intervention they also demonstrated some expressions of cultural identity. In conclusion, although Malaysian private universities’ graphic design education curricula are underpinned especially by Bauhaus principles of design, MCAF related learning activities should be conducted. This study has found that planned interventions within the graphic design classroom can enhance the understanding and the knowledge of local cultural art forms, enabling students to put forward meaningful expressions of cultural identity.